The Concepts of Identification and Identity in Criminalistics - Ioan Aron (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2022)
The term "identity" expressed in a more simplistic form can be reduced to the fact that a being, an object or phenomenon is identical only to itself with the specification that this manifestation is rendered objectively only at a given moment, in a certain form , because over time and under the action of external factors they can change, but they retain their unique fundamental characteristics that define them.